Pengembangan CMS (Content Management System) dalam Pembuatan Website Jurusan Menggunakan Framework Laravel - Subiksa, Gde Brahupadhya; Peling, Ida Bagus Adisimakrisna; Ariawan, Made Pasek Agus; Suardani, Luh Gede Putri (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 11 No 4 (2023): JELIKU Volume 11 No 4, May 2023DO - 10.24843/JLK.2023.v11.i04.p33, 2023)
Every institution currently has a website, this is because the website is easily accessible and available on various devices such as smartphones, tablets, laptops, or even computers. As mentioned above, with a website as an electronic information medium, it will simplify the process of conveying and sending information. Bali State Polytechnic is one of the campuses that wants to implement this, especially in the Department of Electrical Engineering. At this time the website for the Electrical Engineering Department still uses the WordPress CMS, which from a security point of view is still lacking, especially if you use a lot of plugins provided by third parties. The number of plugins used on the created website can slow down the page loading process with the WordPress CMS. Departing from these problems, the author wants to propose a database design that will later be used in making the website for the Department of Electrical Engineering, State Polytechnic of Bali. Based on the results of the research that has been done, it can be concluded that the development of a content management system (CMS) using the Laravel framework can be implemented on the website of the Department of Electrical Engineering, Bali State Polytechnic with an overall good rating of 86% and very good of 14%